2010
DOI: 10.1039/b923122f
|View full text |Cite
|
Sign up to set email alerts
|

Octa, deca, and dodeca(4-nitrophenyl) cage silsesquioxanes via 4-trimethylsilylphenyl derivatives

Abstract: Pure octa, deca, and dodeca(4-nitrophenyl) cage silsesquioxanes were obtained by regio-selective 4-nitration of octa, deca, and dodeca(4-trimethylsilylphenyl) cage silsesquioxanes via ipso-substitution of trimethylsilyl-phenyl bonds by fuming nitric acid. 3-Nitration of octa(4-methylphenyl)octasilesquioxane was also described. The starting octa(4-methyl-, 4-isopropyl- and 4-trimethylsilylphenyl)octasilsesquioxanes were selectively formed in 9-21% isolated yield in the presence of hydrochloric acid. Mixtures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…As already discussed, Olsson and Laine have reported the preparation of a mixture of functionalized T 8 compounds through electrophilic substitution reactions like nitration or bromination of phenyl rings [15,16]. However, the selectivity was not well-controlled.…”
Section: Octa(4-bromo-substituted Phenyl)-t 8 From Condensatementioning
confidence: 96%
See 1 more Smart Citation
“…As already discussed, Olsson and Laine have reported the preparation of a mixture of functionalized T 8 compounds through electrophilic substitution reactions like nitration or bromination of phenyl rings [15,16]. However, the selectivity was not well-controlled.…”
Section: Octa(4-bromo-substituted Phenyl)-t 8 From Condensatementioning
confidence: 96%
“…Acetic acid (0.37 g, 6.24 mmol) was added dropwise to THF (30 mL) dispersion of sodium 4-bromo-substituted phenylcyclotetrasiloxanolate (1.0 g, 1.04 mmol), reported by Pizzotti et al [16]. After stirring for 2 h, water (200 mL) and ether (100 mL) were added to the reaction mixture.…”
Section: Synthesis Of 4-bromo-substituted Phenyl-t 8 From Sodium Hydrmentioning
confidence: 99%
“…Especially, when both T 10 and T 12 compounds have similar chemical and physical properties, it is difficult to find a simple method of their separation. 12 Moreover, separation of cage-like compounds 15 possessing different numbers of side-chains is also cumbersome. For instance, Laine et al pointed out that styrenyl-functionalized cage silsesquioxanes exhibited the same retention times during chromatographic purification, although they had different numbers of phenyl substituents.…”
Section: Introductionmentioning
confidence: 99%
“…For 30 example, Kawakami et al reported the formation of T 8 , T 10 and T 12 cages (octa-, deca-, and dodeca-4-nitrophenyl cage silsesquioxanes) during hydrolysis of 4-substitutedphenyltriethoxysilane in the presence of tetrabutylammonium fluoride (TBAF). 15 To obtain pure fractions, various 35 crystallizations using acetonitrile/THF (v/v, 1:1), hexane, and ethanol/hexane (v/v, 1:4) systems were carried out, and each fraction was purified by further recrystallization. Also, Laine et al, inspired by the Kawakami procedure, utilized it for T 10/12 stilbenevinyl-silsesquioxane separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation